Ki67 and the apparent diffusion coefficient in postoperative prostate cancer with endocrine therapy - He, Jun; Che, Bangwei; Li, Po; Li, Wei; Huang, Tao; Chen, Peng; Liu, Miao; Li, Guangyu; Zhong, Siwen; Tang, Kaifa (Frontiers in Surgery, 2023)
Background: Prostate-specific antigen (PSA) is a critical part of prostate cancer (Pca) screening, diagnosis, staging, and prognosis. However, elevated PSA levels can also be affected by several external factors. To improve specificity and sensitivity of PSA in clinical practice, we explore whether marker or parameter may be used as a prognostic target for Pca by a long-term follow-up. Methods: A total of 121 Pca patients who underwent laparoscopic radical prostatectomy (LRP) were included in our study, along with imaging and preoperative pathological diagnosis. Endocrine therapy has been applied to treat postoperative patients for a long time. The prognosis of enrolled patients was followed, and statistics were collected. The spearman correlation was applied to examine the relationship and clinical parameters. Kaplan-Meier analysis was used to process clinical variables of Pca patients. Cox proportional hazards regression analysis was applied to examine univariate and multivariate variables. Results: GS, PSA, clinical stage, nerve infiltration, organ confined, Ki67 and apparent diffusion coefficient (ADC) were significantly associated with prognosis (all P＜0.05). GS, PSA, clinical stage, organ confined, Ki67, nerve infiltration and ADC were included in the multivariate analysis (all P＜0.05). In final , Ki67 and ADC may provide several meaningful predictive information (both P＜0.05). Conclusions: Ki67 and ADC may provide clinically and analytically valid prognostic biomarker and imaging parameter in Pca. They may bring some approachs to predict the prognosis and risk of the Pca patients receiving postoperative routine endocrine therapy.